Voluntary Inhibitory Control of Chorea: A Case Series. Issue 3 (20th February 2020) - Bonomo, Roberta; Latorre, Anna; Balint, Bettina; Smilowska, Katarzyna; Rocchi, Lorenzo; Rothwell, John C.; Zappia, Mario; Bhatia, Kailash P.
ABSTRACT: Background: Volitional control of involuntary movements has so far been considered a hallmark of tic disorders. However, modulation of involuntary movements can also be observed in other hyperkinesias. Cases: Here, we present 6 patients with chorea able to suppress their involuntary movements, on demand. In 3 of them, surface electromyography was used to quantify degree of suppression and confirmed a reduction of muscle activity up to 68%, during volitional control. Conclusion: This observation represents a first step toward a description of a new clinical feature in choreic syndromes and an opportunity to redefine the role of volitional inhibition in hyperkinetic movement disorders. Abstract : View Supplementary Video